Organization theory : modern, symbolic, and postmodern perspectives - Hatch, Mary Jo.; Cunliffe, Ann L. (Oxford, United Kingdom : Oxford University Press, 2013)
'Offers a clear and comprehensive introduction to the study of organizations and organizing processes. It encourages an even-handed appreciation of the different perspectives contributing to our knowledge of organizations and challenges readers to broaden their intellectual reach.'--Publisher description.
Includes bibliographical references and index.
Keywords: Organizational behavior; Organizational sociology; Organization